2019
DOI: 10.1371/journal.pgen.1008430
|View full text |Cite
|
Sign up to set email alerts
|

The effects of manipulating levels of replication initiation factors on origin firing efficiency in yeast

Abstract: Chromosome replication in Saccharomyces cerevisiae is initiated from ~300 origins that are regulated by DNA sequence and by the limited abundance of six trans-acting initiation proteins (Sld2, Sld3, Dpb11, Dbf4, Sld7 and Cdc45). We set out to determine how the levels of individual factors contribute to time of origin activation and/or origin efficiency using induced depletion of single factors and overexpression of sets of multiple factors. Depletion of Sld2 or Sld3 slows growth and S phase progression, decrea… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 85 publications
(150 reference statements)
4
19
0
Order By: Relevance
“…These mutants would be forced to use late origins under HU to survive. This is also consistent with the observation that the peak widths on average for these slow growing mutants was larger than WT peak heights because the smaller number of origins utilized would not be restrained by rate-limiting replication factors, which are known to exist 16,17 . We suggest that the mutations at Orc4 R478 and N489 would not cause sequence specificity changes but instead cause inefficient binding to origins.…”
Section: Resultssupporting
confidence: 89%
“…These mutants would be forced to use late origins under HU to survive. This is also consistent with the observation that the peak widths on average for these slow growing mutants was larger than WT peak heights because the smaller number of origins utilized would not be restrained by rate-limiting replication factors, which are known to exist 16,17 . We suggest that the mutations at Orc4 R478 and N489 would not cause sequence specificity changes but instead cause inefficient binding to origins.…”
Section: Resultssupporting
confidence: 89%
“…We propose that rDNA copy number reduction will affect genome replication only if the rDNA replication timing is affected. This proposal is supported by our earlier studies describing a mutant that induces replication stress and reduces rDNA copy number (250 to 90) (SLD3-AID, (Lynch et al, 2019)). The reduced rDNA array remained late replicating, possibly because its copy number reduction did not suffice to alter replication timing.…”
Section: Discussionsupporting
confidence: 67%
“…While ribosome deficiencies do result when rDNA copy number drops below a threshold (Delany et al, 1994;French et al, 2003;Ritossa and Atwood, 1966;Sanchez et al, 2017), several other phenotypes have been associated recently with more physiologically relevant rDNA copy number variants that are sufficient for ribosome biogenesis (Gibbons et al, 2014;Ide et al, 2010;Lu et al, 2018;Michel et al, 2005;Paredes et al, 2011;Picart-Picolo et al, 2020;Wang and Lemos, 2017;Xu et al, 2017). Additionally, the plastic nature of the rDNA locus allows copy number fluctuations in the face of stressors such as nutrient availability (Aldrich and Maggert, 2015) or replication defects (Ide et al, 2007;Lynch et al, 2019;Salim et al, 2017;Sanchez et al, 2017). We were intrigued by the rDNA reductions seen in the presence of replication stress, which strongly suggested that rDNA copy number variation might directly influence replication of the genome.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous work supports a model in which multiple MCMs are loaded at origins (Das et al, 2015;Yang et al, 2010). Furthermore, overexpression of origin-activating factors in S phase causes most all origins to fire early in S phase, consistent with most origins having at least one MCM loaded (Lynch et al, 2019). Our MNase approach to MCM ChIP-seq reported here further supports the multiple-MCM model by producing high-resolution maps of MCM locations that identify MCMs at multiple locations across origins.…”
Section: Discussionsupporting
confidence: 86%